Analisis Bahaya Banjir Sungai Bone-Bone dengan Metode Geographical Information Sistem (GIS) Pada Daerah Bantimurung Kecamatan Bone-Bone Kabupaten Luwu Utara Provinsi Sulawesi Selatan: Flood Hazards Analysis of the Bone-Bone River with Geographical Information System Method (GIS) in Bantimurung Area, Bone-Bone District, North Luwu Regency South Sulawesi Province - Rohaya Langkoke; Andi Zarkia Nur (Universitas Hasanuddin, 2022)
ABSTRACT The research area is included in the Malili Sheet, located in the Bone-Bone River Sub-watershed, Bantimurung District, Bone–Bone District, Luwu Regency, South Sulawesi Province with coordinates 120o29'00” east longitude – 120°34'00” east longitude and 2°30'00 “LS – 2°37'00” South. In general, this study aims to determine the causes of flood hazards by using the field survey method and data management with geographic information systems (GIS), Analytical Hierarchy Process (AHP) weighting, and potential flooding in the research area. The parameters used in making the map are slope maps, elevation maps, land use maps, distance maps to rivers, and rainfall maps. The results of the flood hazard map showed the highest hazard level of 7.32% of the research area or 5.56 km2. But the map is dominated by a low hazard level of 73.01% of the total area of 55.49 km2. Based on field observations, several factors that can cause flooding at the research location are the results of landslides in the river body, which can cause river silting. ABSTRAK Daerah penelitian termasuk dalam Lembar Malili yang terletak di Sub-DAS Sungai Bone-Bone, Kecamatan Bantimurung, Kabupaten Bone-Bone, Kabupaten Luwu, Provinsi Sulawesi Selatan dengan koordinat 120o29'00” BT – 120°34'00” Bujur Timur dan 2°30'00 “LS – 2°37'00” Selatan. Secara umum penelitian ini bertujuan untuk mengetahui penyebab bahaya banjir dengan menggunakan metode survei lapangan dan pengelolaan data dengan geographic information systems (GIS), pembobotan AHP (Analytical Hierarchy Process) dan potensi banjir di daerah penelitian. Parameter yang digunakan dalam pembuatan peta adalah peta kemiringan lereng, peta elevasi, peta tata guna lahan, peta jarak ke sungai, dan peta curah hujan. Hasil peta kerawanan banjir menunjukkan tingkat kerawanan tertinggi sebesar 7,32% dari luas daerah penelitian atau 5,56 km2. Tetapi peta tersebut didominasi oleh tingkat bahaya rendah sebesar 73,01% dari luas total 55,49 km2. Berdasarkan observasi lapangan, beberapa faktor yang dapat menyebabkan banjir di lokasi penelitian adalah akibat longsoran di badan sungai yang dapat menyebabkan pendangkalan sungai.